NUTRITIONAL ASSESSMENT IN VITAMIN D DEFICIENT CHILDREN GROUPS IN FEDERAL AREA OF PAKISTAN - Manaish Kumar; Afsheen Mansoor; Edwin C. Cancino; Muhamad Babur; Osama Ahmad; Joti Devi; Saima Zaib; Madieha Ambreen; Shahrukh Irfan; Mehvish Mushtaq (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
Vitamin D deficiency is a global health concern affecting children worldwide, including those residing in the Federal Area of Pakistan. This research article aims to investigate the nutritional status of children in this region and assess the prevalence of vitamin D deficiency among them. We conducted a cross-sectional study involving a sample of children aged 1 to 18 years. A total of 500 children aged 1 to 18 years were selected using a stratified random sampling technique. Data on dietary habits, sunlight exposure, anthropometric measurements, and serum vitamin D levels were collected. The results of this study underscore the urgent need for public health interventions to combat vitamin D deficiency in children in the Federal Area of Pakistan.